Effectiveness of Rice Water and Clam Shells on Red Chili Plants (Capsicum annuum L.) Growth - Umroh, Devi Mauliya; Ratnasari, Evie (LenteraBio : Berkala Ilmiah Biologi, 2024)
Red chili (Capsicum annuum L.) are vegetables frequently used in cooking. However, their supply often falls short of market demand. Inorganic fertilizers are commonly used to enhance plant productivity, but their excessive use can damage soil and agricultural ecosystems, and they are relatively expensive. This study aims to evaluate the effectiveness of rice water and clam shells on the growth of red chili, including plant height, number of leaves, and stem diameter. This aligns with the SDGs' goals of zero hunger and responsible consumption and production by utilizing waste as fertilizer to boost plant growth. The research design employed a Randomized Block Design with treatment of rice water and clam shells concentrations at 0%, 10%, 20%, 40%, 60%, and 80%, along with NPK + ZA fertilizer, with four replications. The data obtained were analysed using one-way ANOVA, and Duncan's test was to compare means between treatments. The results indicated that the application of rice water and clam shells at different concentrations, as well as NPK + ZA fertilizer, significantly affects plant height but does not impact the number of leaves or stem diameter. The optimal treatment was found to be 80% concentration of liquid organic fertilizer.